2013
DOI: 10.1128/aac.01629-13
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Eight Antifungal Drugs against 106 Waterborne and Cutaneous Exophiala Species

Abstract: The in vitro activities of eight antifungal drugs against 106 clinical and environmental isolates of waterborne and cutaneous Exophiala species were tested. The MICs and minimum effective concentrations for 90% of the strains tested (n ‫؍‬ 106) were, in increasing order, as follows: posaconazole, 0.063 g/ml; itraconazole, 0.25 g/ml; micafungin, 1 g/ml; voriconazole, 2 g/ml; isavuconazole, 4 g/ml; caspofungin, 8 g/ml; amphotericin B, 16 g/ml; fluconazole, 64 g/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 23 publications
4
20
1
Order By: Relevance
“…Finally, we have established antifungal susceptibility profiles for a representative selection of 50 of the test panel isolates. In agreement with several previous reports of human-pathogenic Exophiala species (17,27), the amphotericin B and triazole MICs with our Exophiala isolates were generally low (17,27) and lower than those for the echinocandins (18). In the current study, only a limited number of isolates exhibited in vitro resistance to amphotericin B, in contrast to previous analyses employing waterborne isolates and those from cutaneous infections in predominantly cold-blooded animals (18).Unfortunately, very few of the waterborne Exophiala species and those associated with infections in cold-blooded animals were represented in our collection, precluding a direct comparison in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Finally, we have established antifungal susceptibility profiles for a representative selection of 50 of the test panel isolates. In agreement with several previous reports of human-pathogenic Exophiala species (17,27), the amphotericin B and triazole MICs with our Exophiala isolates were generally low (17,27) and lower than those for the echinocandins (18). In the current study, only a limited number of isolates exhibited in vitro resistance to amphotericin B, in contrast to previous analyses employing waterborne isolates and those from cutaneous infections in predominantly cold-blooded animals (18).Unfortunately, very few of the waterborne Exophiala species and those associated with infections in cold-blooded animals were represented in our collection, precluding a direct comparison in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Limited previous studies have suggested that Exophiala spp. might exhibit certain species-specific antifungal susceptibility variations, in particular with respect to amphotericin B (17,18,27). Thus, a selection of 50 isolates in the current study were subjected to antifungal susceptibility testing against a panel of antifungal agents covering most drug classes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the full range of species against which isavuconazole has activity and the clinical breakpoints have not yet been established. Nevertheless, previous studies have demonstrated MIC values of ≤4 μg/mL for many species closely related or identical to the rare pathogens in the current study . Although some isolates in the current study appeared to have reduced susceptibility in vitro compared with those prior studies, we cannot exclude the possibility of cross‐resistance in some patients who failed prior antifungal therapy.…”
Section: Discussioncontrasting
confidence: 74%
“…Combination antifungal therapy is recommended for disseminated infections in immunocompromised patients . Historically, itraconazole, voriconazole, posaconazole, and AmB have shown the most consistent activity against Exophiala species, but recent data suggest that antifungal susceptibility differs between species .…”
Section: Discussionmentioning
confidence: 99%